Por amor ao mundo: educação e direitos humanos segundo Hannah Arendt - Farias, Ana Santana Batista (2021)
The present work intends to analyze the political-philosophical reflections of Hannah Arendt, looking back to detect the constituent threads of her conceptual web, capable of founding the universal pillars inherent to education and the foundational validity of human rights, in the Arendtian perspective. The research path traced, first, ascertains the recent challenging historical context of human rights education in Brazil, marked by the regression of the Brazilian State in the fulfillment of the progressive human rights agenda. In a second step, starting from the bibliographic study of Arendt's main works, the repercussions on education and human rights, brought about by the crisis of the modern world, brought about by the great misfortune left by the totalitarian regimes that occurred in the century, are brought to light XX. Subsequently, it is intended to emerge, according to Arendtian reflection, the common founding elements of education and human rights, namely: responsibility, tradition and plurality, with the task of understanding them as contributory gems for a new perspective of rights education human beings, assurance that the binding promise of protecting human dignity resides in everyone's responsibility for the common world, based on human plurality, even in dark times like the ones we experience in the current scenario of Brazilian education.